2005
DOI: 10.1103/physrevlett.95.123901
|View full text |Cite
|
Sign up to set email alerts
|

Vortex Transmutation

Abstract: Using group theory arguments and numerical simulations, we demonstrate the possibility of changing the vorticity or topological charge of an individual vortex by means of the action of a system possessing a discrete rotational symmetry of finite order. We establish on theoretical grounds a "transmutation pass" determining the conditions for this phenomenon to occur and numerically analyze it in the context of two-dimensional optical lattices. An analogous approach is applicable to the problems of Bose-Einstein… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
79
0
1

Year Published

2012
2012
2021
2021

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 73 publications
(80 citation statements)
references
References 15 publications
0
79
0
1
Order By: Relevance
“…In addition, we have revealed that incoherent interactions may result in new composite solitons being either a four-lobe DFS or a ring-DVS. These rich interactions open up new prospects for all-optical routing by designing the interactions between different higher-order solitons [39], and soliton-controlling in other nonlinear periodic structures such as photonic crystals [40] and Bose-Einstein condensates [41].…”
Section: Resultsmentioning
confidence: 99%
“…In addition, we have revealed that incoherent interactions may result in new composite solitons being either a four-lobe DFS or a ring-DVS. These rich interactions open up new prospects for all-optical routing by designing the interactions between different higher-order solitons [39], and soliton-controlling in other nonlinear periodic structures such as photonic crystals [40] and Bose-Einstein condensates [41].…”
Section: Resultsmentioning
confidence: 99%
“…The effect of such a rotation is the adding of m times the same angle to its phase [30,60]. It was shown that the values of m are restricted by the order of symmetry [28], and hence,…”
Section: Vortices In a Weakly Interacting Bose-einstein Condensatementioning
confidence: 99%
“…It was also shown that one can relate the angular momentum of a circularly symmetric vortex struck by a discretly symmetric potential of order N with the angular pseudomomentum m of the wave function in the discrete symmetry media by the transformation rule [28][29][30],…”
Section: Vortices In a Weakly Interacting Bose-einstein Condensatementioning
confidence: 99%
See 1 more Smart Citation
“…36,37. Discrete vortex solitons can also be created in photonic crystal fibers and other types of photonic lattices 38,39 . Discrete vortex solitons are frequently associated with soliton clusters, which feature interesting mobility properties and rotating propagation [29][30][31][40][41][42] .…”
Section: Introductionmentioning
confidence: 99%